Virtual Classroom Assessment for Children and Adolescents With Attention Deficits: A Systematic Review and Meta-Analysis of Measurement Properties. Issue 3 (February 2021) - Gilboa, Yafit; Fogel-Grinvald, Haya; Chevignard, Mathilde
Objective: The virtual classroom (VC) is a head-mounted display immersive system for the assessment of attention. A meta-analysis was performed to examine the use of the VC to assess attention in children and adolescents.Method: We conducted a systematic literature search to select articles up to December 2017.Results: Thirteen studies using the VC to assess attention were included. Studies reporting comparisons between patients with various clinical conditions and healthy controls were included in the meta-analysis. The meta-analysis results revealed significant differences between groups for the percentage of identified targets (nine studies; total combined N = 431), for commission errors, and reaction time (eight studies; total combined N = 399) in favor of the nonclinical group.Conclusion: Preliminary evidence establishes the validity of the VC and suggests that this task has the potential to serve as a useful and enjoyable ecological assessment tool for the diagnosis of attention deficits in children and adolescents. (J. of Att. Dis. XXXX; XX(X) XX-XX)